MANIFESTATION OF THE SPIRIT OF FEMINISM AS REFLECTED IN BARBIE AND FAIRY SECRET THE MOVIE - Amala, Heni Nur (Jurnal Ilmiah Mahasiswa FIB, 2013)
Nowadays, film becomes very popular as one of favorite entertainments among people. There are a lot of genres in movie, for example drama, thriller, action, etc. Some of them take fairytale or fiction story to be filmed. Fairy tale stories portrayed prince and princess as the main characters. But modern fairytale portrayed female domination on the story. The writer conducts a study about the manifestation of the spirit of feminism as reflected in the movie Barbie and Fairy Secret. There is a problem to be solved, it is how Barbie as the main character in the movie manifests the concept of the spirit of feminism.This study uses qualitative approach in relation to analyze the object material. To figure out the research question, the writer uses Feminist Criticism which employs three concepts, they are Third Wave Feminism Patriarchal combined with Traditional Gender Role, and Gender Equality. Each approach has a particular role to help the writer reveals the spirit of feminism manifested in Barbie character.This study uncovers Barbie’s experience in both of femininity and equality related to the spirit of feminism. Barbie is a successful actress who has to save her boyfriend who kidnap. She goes to the fairy world to save him. She through some obstacles and fights the fairy princess. Furthermore, she is helped by other fairies and accompanied her to the fairy world. Barbie can save her boyfriend and the story ends with happy ending scene. Here, Barbie learns that woman does not have to change like man to be equal. Moreover, her character has different role in carrying the spirit of feminism in terms of equality.The writer has identified that there is a shifting role between male and female character in a fairy tale movie which is different with ordinary stories that exist for ages. This study analyze about Barbie who has different role in carrying the spirit of feminism in terms of equality in the movie by using three concepts above. The writer suggests the next researchers to use either Deconstruction or Marxism in using Barbie and Fairy Secret movie as the material object of the research.